Tithonia (Tithonia diversifolia) foliage meal in integral diets for lactating calf feeding: preliminary economical results - Cino, Delia Mar?a; Ruiz, Tom?s E.; Mart?nez, Y.; Chongo, Bertha; D?az, Humberto (Cuban Journal of Agricultural Science, 2012)
The economical possibilities of using Tithonia diversifolia as forage meal in integral diets for lactating calves were evaluated from experimental data of the Institute of Animal Science (Ruiz et al. 2008 and Mart?nez 2009). Elements involving sowing and establishment as forage species and for grazing were collected. Cost data cards were organized indicating preparation, sowing and forage cut expenses to estimate the cost per ton of forage and as foliage meal. The inclusion of different meal levels were evaluated economically in diets for crossbred dairy calves of 40 kg (30 to 120 days of age) with ground hay of Cynodon nlemfuensis in 4 treatments: T1 ID (integral diet) + 20% hay, T2 ID+ 5% hay + 5% Tithonia meal, T3 ID + 10% hay + 10% Tithonia meal and T4 ID + 15% hay + 15% Tithonia meal. In all treatments 4 liters of milk were supplied from 30 to 60 days of age. Cost data cards were estimated per treatment and the indicators: production value, cost/animal/day per kg live weight, Benefit/cost ratio, variable expenses/incomes, gross margin/animal and economical profitability. The Northamerican dollar (USD) was used as money standard. The cost per t of forage was of 4.26 and 128.40 the t of meal. Treatments including meal recorded the lowest costs/animal/day, per kg LW and per and higher benefit/cost ratio. T4 also showed lower percentage of income utilization to cover its variable expenses, higher net income level, gross margin/animal and economical profitability. Results although preliminary showed the economical possibilities of using T. diversifolia forage meal in diets for lactating calves with a greater utilization of natural resources and, in this way, savings for the economy of the country. Key words: Tithonia diversifolia, forage meal, lactating calves, economical analysis